Disability pension due to musculoskeletal diagnoses: importance of work-related factors in a prospective cohort study of Finnish twins - Sanna Kärkkäinen; Janne Pitkäniemi; Karri Silventoinen; Pia Svedberg; Antti Huunan-Seppälä; Karoliina Koskenvuo; Markku Koskenvuo; Kristina Alexanderson; Jaakko Kaprio; Annina Ropponen (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: The aim of this study was to investigate the impact of work-related risk factors for future disability pension (DP) due to musculoskeletal diagnoses and for a subgroup of these, namely, DP due to osteoarthritis. METHODS: For this prospective study of 16 028 Finnish twins born in 1911-1957 and employed at baseline, a postal questionnaire collected information in 1975 on work-related factors; follow-up data on DP was gathered through register linkages up to 2004. A series of proportional hazards (Cox) regression models were used to analyze the associations between work-related factors and the incidence of DP. RESULTS: During the 30-year follow-up, 1297 participants (8%) were granted DP due to musculoskeletal diagnoses, 376 of which were due to osteoarthritis. High stress of daily activities, monotonous work, physical workload (namely work including lifting and carrying or physically heavy work), several workplace changes, and unemployment displayed a strong association with DP due to musculoskeletal diagnoses that was not affected by familial factors, including genetics and shared environment. Additionally, standing work increased the risk for DP due to osteoarthritis. CONCLUSIONS: Uninfluenced by family background or other confounding factors, several work-related factors were identified as being strong and direct risk factors for DP due to musculoskeletal diagnoses.